Enlight: A consensus checklist for reporting laboratory-based studies on the non-visual effects of light in humans - Spitschan, Manuel (2023)
Background: There is no consensus on reporting light characteristics instudies investigating non-visual responses to light. This project aimed todevelop a reporting checklist for laboratory-based investigations on the impactof light on non-visual physiology.Methods: A four-step modified Delphi process (threequestionnaire-based feedback rounds and one face-to-face group discussion)involving international experts was conducted to reach consensus on the itemsto be included in the checklist. Following the consensus process, the resultingchecklist was tested in a pilot phase with independent experts.Findings: An initial list of 61 items related to reporting light-basedinterventions was condensed to a final checklist containing 25 items, basedupon consensus among experts (final n = 60). Nine items were deemed necessaryto report regardless of research question or context. A description of eachitem is provided in the accompanying Explanation and Elaboration (E&E)document. The independent pilot testing phase led to minor textualclarifications in the checklist and E&E document.Interpretation: The ENLIGHT Checklist is the first consensus-based checklistfor documenting and reporting ocular light-based interventions for humanstudies. The implementation of the checklist will enhance the impact oflight-based research by ensuring comprehensive documentation, enhancingreproducibility, and enabling data aggregation across studies.